Te Umutaoroa, Patuheuheu and Ngāti Haka: Towards a Prophetic Model for Unity and Transformation - Rangiwai, Byron (Te Kaharoa, 2011)
This article explores the emergence of a prophecy called Te Umutaoroa (earth oven of long cooking), given to Patuheuheu and Ngāti Haka by Te Kooti Arikirangi - a nineteenth century Māori leader whom the government wanted to eliminate. This was a discourse uttered by Te Kooti in 1886 and promised the restoration of all that was taken away from Patuheuheu and Ngāti Haka in the mid 1880s and beyond. This article asserts that Te Kooti was both a prophet and transformational leader. This work is the beginning of a framework for hapū development based on the eight parts or promises contained within Te Kooti’s Te Umutaoroa prophecy. The purpose of this work is to scope out the ‘bones’ of a framework which aims for complete unity between Patuheuheu and Ngāti Haka, and through the united efforts of both hapū, development and positive transformation in the various contexts of the Waiohau community.